IMPACT : Destruction from the Air - Consulting Editor Parton, James and Sponsored by the Air Force Historical Foundation (New York James Parton and Co., 1989)
PART OF A SERIES OF THE ARMY AIR FORCES' "CONFIDENTIAL" PICTURE HISTORY OF WORLD WAR II. THIS BOOK FEATURES THE AUGUST 1943, SEPTEMBER 1943 AND OCTOBER 1943 EDITIONS ON THE EUROPEAN AND PACIFIC WAR.
Includes Index and Colored Illustrations.
Keywords: Air warfare -- Pictorial works